An Updated Review of the Pre-Clinical Role of microRNAs and their Contribution to Colorectal Cancer - Dastmalchi, Narges; Safaralizadeh, Reza; Teimourian, Shahram (Current Molecular Medicine, 2022)
Colorectal cancer (CRC) is one of the main causes of malignancy-related mortality worldwide. It was well-identified that microRNAs (miRNAs) decisively participate in cellular biological pathways; in a way that their deregulated expression causes CRC progression. miRNAs can control the translation and degradation of mRNAs by binding to various molecular targets involved in different biological processes, including growth, apoptosis, cell cycle, autophagy, angiogenesis, metastasis, etc. The functions of these dysregulated miRNAs may be either oncogenic or tumorsuppressive. Therefore, these miRNAs can be contributed to prognostic, diagnostic, and therapeutic approaches in CRC. In this study, we reviewed the tumor-suppressive and oncogenic functions of miRNAs in CRC and assessed their molecular activities in CRC development. However, further investigation for the involvement of dysregulated miRNAs in CRC progression is required.
Keywords: MicroRNA